Evaluation of mobile clinics by MSF in pastoralist community in Doolo Zone, Somali region, Ethiopia - Birhanu Sahelie; Luke Baertlein; Bashir AIi Dubad; Mohammed Osman; Nathan Post; Beverley Stringer; Turid Piening; Hanna Majanen; Istifanus Chindong Damulak; Elburg Van Boetzalaer; Anna Kuehne; Patrick Keating (BMC Health Services Research)
Abstract Background The Somali region in Ethiopia has poor health infrastructure, coupled with the adversity experienced by the largely pastoralist population through frequent droughts, disease outbreaks and conflict. From January 2019, MSF strategically focused on improving access to primary healthcare in the Doolo zone of the Somali region by providing 15–20 mobile clinics covering a wide geographical area. We aimed to evaluate the extent to which mobile clinics were an appropriate and effective modality to deliver healthcare for populations living in the region. Methods In this mixed-methods study, we conducted a descriptive analysis of 24 months of routine mobile clinic data (February 2019 to January 2021) to evaluate the appropriateness and effectiveness of mobile clinics. We conducted a patient satisfaction survey to assess perceived benefits and challenges, as well as seven interviews with MSF medical staff and four focus group discussions with community members from mobile clinic sites to explore the appropriateness, effectiveness, and connectedness of mobile clinics. Results MSF mobile clinics conducted 90,542 outpatient consultations, across 30 mobile clinic sites during the two-year period. However, there were gaps in continuity of care. The ratio of follow-up-to-first antenatal care visits was 0.82, and the ratio of third-to-first dose of DTP/Hib/HepB vaccine was 0.39. The current mobile clinic strategy is generally well perceived by the community in terms of the quality of services provided. However, MSF staff and community members expressed that its appropriateness and effectiveness are limited by mobile clinic opening hours, large patient volumes, referral policies, staffing, and drug supply issues. Conclusions Limited opening hours, large patient volumes, weak referral processes and supply issues impacted the appropriateness and effectiveness of healthcare provision by mobile clinics to this pastoralist population. These challenges are consistent with those faced by mobile clinics in other contexts. To enhance the effectiveness and appropriateness of mobile clinics for pastoralist populations requires collaboration with both community members and local authorities to design and regularly review the locations, frequency, healthcare service package and referral policies of mobile clinics.